rozwiąż równanie
2(x+3)=-2(2x+1)-4
6x+5-3x=4x+3-2x
5+4(3x-2)=10x-3
6x+5-3x=4x+3-2x
proszę o pomoc​


Odpowiedź :

Odpowiedź:

2 (x+3) = - 2( 2x+1) -4

 2x+6 = -4x -2 -4

     2x+4x = - 2 - 4 -6

 6x= -12 /:6

  x= - 2

 6x + 5 -3x = 4x +3 -2x

     6x- 3x -4x + 2x= 3 - 5

    8x - 7x = - 2

           x= - 2

5 + 4 ( 3x-2 )  = 10 x - 3

    5  +12x -8= 10x -3

   12x - 10x  = - 3 +8-5

      2x =  0

        x= 0

6x +5 -3x= 4x  +3 - 2x

   6x-3x -4x+2x= 3-5

           x= -2

( ten przykład jest drugi raz powtórzony)

Szczegółowe wyjaśnienie: